Effect of Various Concentration of Vegetable Protein in Hair Mask on The Hair Texture - Helen, Ivony; Hadinoto, Idajani; Hadisoewignyo, Lannie; Soegianto, Lisa (Indonesian Research Gateway, 2011)
Effect of various concentrations of vegetable protein in hair mask on the hair texture including hair smoothness, hair shining, hair strength, and morphology of hair had been studied. Concentrations of vegetable protein are made 5%, 7.5%, and 10%. The hair mask was evaluated such as organoleptic, pH, viscosity, and allergy test. Hair mask used in six subjects that have damage hair for 8 times every 2 days. Then, the hair mask was evaluated such as hair smooth and hair shine that used tree trained panel and analyzed using non parametric method Q Cochran. Hair strength was evaluated using autographÃÂ thenÃÂ theÃÂ resultsÃÂ wereÃÂ ÃÂ ÃÂ analyzesÃÂ usingÃÂ ANOVAÃÂ testÃÂ (p<0.05),ÃÂ whileÃÂ hair morphologyÃÂ wasÃÂ evaluatedÃÂ usingÃÂ scanningÃÂ microscopeÃÂ electronÃÂ (SEM).ÃÂ The experimentalÃÂ resultsÃÂ showedÃÂ thatÃÂ vegetableÃÂ proteinÃÂ inÃÂ hairÃÂ maskÃÂ increasedÃÂ hair smoothness, hair strength, and morphology of damaged hair but did not give effect for hair shining. Various concentrations of vegetable protein (5%, 7.5%, and 10%) on hair mask given the same effect in hair texture (hair smoothness, hair strength, and hair morphology).